Secular trend of gout incidence in the UK: an age-period-cohort analysis - Michael Doherty; Xiang Ding; Guanghua Lei; Chao Zeng; Jie Wei; Yuqing Zhang; Weiya Zhang; Jing Ye; Na Lu (BMJ Open)
Objectives The incidence of gout in the UK appears to have declined since 2013; however, whether such a trend occurred across participants born in different years (ie, birth cohort) is unknown. We aimed to examine the effects of the birth cohort on gout incidence using an age-period-cohort (APC) model.Design Cross-sectional study.Setting Nationwide data from the UK primary care database.Participants Individuals between 30 and 89 years of age were included. We excluded individuals who had gout history when entering the database and individuals with less than 1 year of continuous follow-up between 1 January 1999 and 31 December 2019.Primary and secondary outcome measures Gout was identified using READ codes assigned by general practitioners. The incidence of gout between 1999–2013 and 2011–2019 was analysed with APC model.Results The incidence of gout between 1999 and 2013 increased with birth cohorts. Compared with those born in 1949–1953 (reference), the age-adjusted and period-adjusted rate ratios (RRs) of incident gout increased from 0.39 (95% CI 0.34 to 0.46) in participants born in 1910–1914 to 2.36 (95% CI 2.09 to 2.66) in participants born in 1979–1983 (p for trend <0.001). In contrast, the incidence of gout between 2011 and 2019 decreased with birth cohorts. Compared with those born in 1949–1953 (reference), the age-adjusted and period-adjusted RRs of incident gout declined from 2.75 (95% CI 2.30 to 3.28) in participants born in 1922–1926 to 0.75 (95% CI 0.65 to 0.87) in participants born in 1976–1980 but then increased slightly to 0.95 (95% CI 0.77 to 1.17) in participants born in 1985–1989.Conclusions The gout incidence between 1999 and 2013 in the UK increased with the birth cohorts and then decreased between 2011 and 2019 except for those born after 1980. Future monitoring is needed to help identify aetiological factors and guide preventive and treatment strategies for gout.